Growth of Saprophytic and Pathogenic Leptospira: Evaluation of Medium, Temperature, Inoculum, and Cost - Finn, Mary A. (1976)
Of four media tested, a tissue culture medium supplemented with a bovine serum albumin-oleic acid complex provided the best leptospiral growth and cost efficiency.